PENGARUH DEBT TO EQUITY RATIO (DER) DAN CURRENT RATIO (CR) TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN ANEKA INDUSTRI YANG TERDAFTAR DI BEI - Adi Dwi Purnomo; Resi Widianti (Universitas La Tansa Mashiro, 2017)
The poor dividend policy causes the stock price to decline, because with the low dividend payout ratio (DPR) it will reduce the confidence level of investors to invest their shares in the company so that their stock demand also decreases. High Debt to Equity Ratio (DER) value indicates that high debt usage is compared with own capital, so the dividend distribution is low. The low Current Ratio (CR) value causes the company's ability to pay its short-term debts poorly. This study aims to determine the condition and influence of Debt to Equity Ratio (DER) and Current Ratio (CR) to Dividend Payout Ratio (DPR) in Aneka Industri company during 2011-2015 period.The research method used is quantitative method with research type descriptive method. Data analysis technique in this research by using descriptive statistical test, classical assumption test, multiple linear regression analysis, and hypothesis test. Population used in this research is Aneka Industri company listed in Indonesia Stock Exchange (BEI) period 2011-2015 with amount 37 company. The sample used is 6 companies using perposive sampling.Based on the results of tests that have been done t test results show that the Debt to Equity Ratio (DER) has a significant negative effect on Dividend Payout Ratio (DPR) where thitung> ttable is -4.679> 2.052 and the value of Current Ratio (CR) t count <ttabel is equal to 1.483 <2.052 and significance value of 0.106> 0.05 which means H0 accepted and H1 rejected, so it can be concluded that the Current Ratio (CR) has no significant effect on Dividend Payout Ratio (DPR). Based on the results of f test, Fcount> Ftable is 16,906> 3,35 and significance value 0.000 <0,05 so it can be concluded that Debt to Equity Ratio (DER) and Current Ratio (CR) together significantly influence Dividend Payout Ratio (DPR).Based on the results and analysis of the data then obtained the minimum value, maximum value, average value, and fluctuations in each company. The management of the company should be able to improve the good financial performance, especially to control the level of Debt to Equity Ratio (DER), Current Ratio (CR), and Dividend Payout Ratio (DPR).